American Palm Cixiid, Myndus crudus Van Duzee (Insecta: Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) - Forrest W. Howard (EDIS)
EENY-389, a 9-page illustrated fact sheet by F. W. Howard, describes a planthopper whose adults feed on various species of palms and is the only known vector for Lethal Yellowing disease in Florida. Includes sections in distribution, description, biology, host plants, damage and economic importance, management, and selected references. Published by the UF Department of Entomology and Nematology, September 2006.